Observation of metal ions adsorption on novel polymeric chelating fiber and activated carbon fiber - Ko, Young Gun; Choi, Ung Su (ELSEVIER, 2007)
In this study, polymeric chelating fiber with good adsorbing capacity (11.4 mequiv./g) and activated carbon fiber with high specific area (1560 M-2/g) were synthesized to compare the adsorption of heavy metal ions on these materials. The adsorption isotherm of various cations on activated carbon fiber and poly (acrylo- amidino diethylenediamine) showed similar adsorption behavior. High adsorptions were found at high pHs. At low pHs, adsorbed H(+)s on the benzene (in the case of activated carbon fiber) and amine groups (in the case of poly(acrylo-amidino diethylenediamine)) blocked activated carbon fiber-metal complex and poly (acryto-amidino diethylenediamine)-metal complex formations. Metal ion adsorption on activated carbon fiber was lower than that on poly(acrylo-amidino diethylenediamine) due to metal crystal growth on poly(acryloamidino diethylenediamine) although activated carbon fiber has high specific area. In the case of anions adsorption, much higher levels of adsorption were observed at lower pHs, but not at higher pHs due to H's. In conclusion, the results suggest that metal crystal growth using functional group on the surface is more effective to remove metal ions in aqueous solution than high specific area. (C) 2007 Elsevier B.V. All rights reserved.